Analisis Reaksi Pasar Terhadap Pengumuman Dividen Perusahaan LQ45 - Handoko, Liza (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
The purpose of this research is to test whether there is a difference in abnormal return and trading volume activity responded to dividend announcement made by companies in Index LQ45. This research conducted using event study method and uses paired sample t-test as the statistic tool. Cum-date dividend was choosed as the event day and thus make 11 days of window period consist of 5 days before cum-date, cum-date, and 5 days after cum-date. The sample consist of 34 companies which in the list of index LQ45 for the year of 2015. The findings in this research show that there is no significant difference between abnormal before the announcement and after the annoucement and there is no significant difference between trading volume activity before the announcement and after the annoucement. Keywords: dividend announcement, abnormal return, trading volume activity, event study.